Disparitas Ratio Decidendi atas Status Objek Sengketa yang Sama dalam Perkara Perdata dan Pidana - Ajeng Althafira Alkansa; Eka Nanda Ravizki (CV Rewang Rencang, 2025)
Corruption as an extraordinary crime continues to evolve, both in terms of the number of cases and the modus operandi used. Disparity refers to the differences in sentences imposed in cases with similar characteristics, which may occur due to differences in juridical and non-juridical considerations. Ratio decidendi is the legal reasoning or basis used by judges in making decisions. This study examines the considerations of judges in the civil case in Decision No. 291/PK/Pdt/2011 and the criminal case in Decision No. 128/PID.SUS-TPK/2023/PNSBY regarding the status of land ownership at Danau UNESA Lidah. The research method used is juridical-normative. Both decisions reveal disparities in the judges' considerations.